2005
DOI: 10.1063/1.1900725
|View full text |Cite
|
Sign up to set email alerts
|

Artifacts in dynamical simulations of coarse-grained model lipid bilayers

Abstract: With special focus on dissipative particle dynamics simulations of anisotropic and complex soft matter, such as lipid bilayers in water, we have investigated the occurrence of artifacts in the results obtained from dynamical simulations of coarse-grained particle-based models. The particles are modeled by beads that interact via soft repulsive conservative forces (as defined in dissipative particle dynamics simulations), harmonic bond potentials, as well as bending potentials imparting stiffness to the lipid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 56 publications
1
59
1
Order By: Relevance
“…The time step used for propagation was 0.0025 ͑and 0.01 for the long time bending modulus calculations͒. While the small time step is important to avoid simulation artifacts in the calculation of the pressure tensor, 33 we found that the resulting curves were virtually the same using either 0.0025 or 0.01 , in which data were collected for over 1500 . Periodic boundary conditions were applied, and interactions followed the minimum-image convention as the model incorporates no long-range forces.…”
Section: A Simulation Protocolmentioning
confidence: 74%
See 1 more Smart Citation
“…The time step used for propagation was 0.0025 ͑and 0.01 for the long time bending modulus calculations͒. While the small time step is important to avoid simulation artifacts in the calculation of the pressure tensor, 33 we found that the resulting curves were virtually the same using either 0.0025 or 0.01 , in which data were collected for over 1500 . Periodic boundary conditions were applied, and interactions followed the minimum-image convention as the model incorporates no long-range forces.…”
Section: A Simulation Protocolmentioning
confidence: 74%
“…Perhaps the disagreement arises from known simulation artifacts in the calculation of the pressure tensor for "soft" mesoscale models, or possibly due to the integration error that accumulates from an ill-defined time step. 33 Efficient DPD simulations have reproduced a qualitatively correct stress profile; in a review of membrane models, Venturoli et al 17 reproduce a stress profile that has the same features as the all-atom simulation. Finally, detailed explicit solvent coarse-grained simulations, such as the MARTINI forcefield 19 and a LJ/GayBerne lipid model, 60 nicely reproduce all-atom stress profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Specializing this equation for a bilayer, we find that dP N /dz = 0, and therefore the normal stress profile should be constant. This physical requirement has been invoked to assess the quality of simulation protocols 49 or stress calculation methods. 50 Its violation in atomistic simulations of lipid bilayers 26,29,30,33 has sparkled some controversy about the role of constraints, as discussed in the previous section.…”
Section: Stress In Lipid Bilayersmentioning
confidence: 99%
“…To illustrate the application to complex fluids, simulations of the same lipid bilayer model studied previously [26,30,31] have been carried out with the new thermostat. Here, the solvent water is represented as before, and each lipid molecule has the form of a 7-bead chain HT 6 in which α-repulsion parameters between hydrophilic "head" beads (H), hydrophobic "tail" beads (T), and "water" beads (W) are chosen to produce the desired behaviour [30].…”
Section: Resultsmentioning
confidence: 99%